VISUAL LITERACY: COMIC STRIPS AS TEACHING MEDIA IN SIMPLE PRESENT TENSE - Setianingsih, Eri; Wiyanah, Sri (ELTR Journal, 2024)
This study aims to measure the effectiveness of using comic strips as learning media for seventh-grade students in Simple Present Tense at SMPN 2 Sewon. The problem in this study was the students' understanding of grammar, especially in simple present tense, was low. This research is Quantitative, with a quasi-experimental pre-test and post-test as the research design. The comic strips used in this study were made by the researcher herself. The sample of this study was seventh-grade students, The total amount was 64 students, who were divided into two classes, namely experiment and control. The experiment class was given treatment in the form of comic strips as teaching media after the pre-test, while the control class was not. The results showed sig. (2-tailed) 0.000 < 0.05 and  (-8.633) <  (-2.039). Based on the result, it can be concluded that there is a significant difference between the learning outcomes in the pre-test and post-test in the experimental class. Comic Strips proved to be effective to be used as teaching media to help students' learning process in English grammar, especially simple present tense.